Tech Giants, Artificial Intelligence and the Future of Journalism - Whittaker, Jason Paul (Taylor & Francis, 2019)
This book examines the impact of the "Big Five" technology companies - Apple, Alphabet/Google, Amazon, Facebook and Microsoft - on journalism and the media industries. It looks at the current role of algorithms and artificial intelligence in curating how we consume media and their increasing influence on the production of the news. Exploring the changes that the technology industry and automation have made in the past decade to the production, distribution and consumption of news globally, the book considers what happens to journalism once it is produced and enters the media ecosystems of the internet tech giants - and the impact of social media and AI on such things as fake news in the post-truth age.